High volume image-guided Injections for patellar tendinopathy: a combined retrospective and prospective case series - Morton, Sarah (CIC Edizioni Internazionali, 2014)
BACKGROUND: the aim was to quantify the effect of a novel high volume-image guided injection (HVIGI) technique for recalcitrant patellar tendinopathy (PT). METHODS: twenty patients (8 prospective; 12 retrospective) with ultrasonographically confirmed proximal PT were recruited. A HVIGI under ultra-sound guidance of 10 ml 0.5% Bupivacaine, 25 mg Hydrocortisone and 30 ml normal saline at the interface of the patellar tendon and Hoffa’s fat pad was administered. A standardised eccentric loading rehabilitation protocol was prescribed. RESULTS: the VISA-P score improved from 45.0 to 64.0 (p<0.01) for all subjects, likely to be clinically significant. There was no statistically significant difference between the increase in the retrospective group of 19.9 (± 23.5) and the prospective of 16.4 (± 11.3) p = 0.7262.5% of prospective subjects agreed that they had significantly improved, with 37.5% returning to sport within 12 weeks. CONCLUSIONS: HVIGI should be considered in the management of recalcitrant PT. Randomised controlled trials are warranted.